النمو الحضري لمدينة سطيف في ضوء السياسات العمرانية المتعاقبة - طاجين عادل; يعلي فروق (University of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى التعرف على سيرورة النمو الحضري في إحدى المدن الجزائرية في ضوء السياسات العمرانية المتعاقبة عبر مختلف المحطات التاريخية التي مرت بها الجزائر، ألا وهي مدينة سطيف التي عرفت تحضرا متسارعا أدى إلى استنفاذ احتياطها العقاري. وأكدت نتائج الدراسة على أن السياسات العمرانية في مدينة سطيف كما في باقي المدن الجزائرية كانت حبيسة الظروف الاقتصادية للبلد، وفي أغلب مراحلها أصبحت مجرد سياسات إسكانية لا غير، مركزة على الكم عوض التركيز على الجودة ونوعية الحياة التي تتماشى والتركيبة الثقافية للمجتمع الجزائري. فرغم الجهود المبذولة من طرف الدولة والأغلفة المالية التي تم رصدها وصرفها إلا أن هذه السياسات العمرانية في مجملها كانت عبارة عن استجابات لمشكلات طارئة للمدينة ما تلبث تلك السياسات الاستعجالية حتى تفرز الكثير من المشكلات الحضرية، لذا يجب إعادة النظر فيها حتى تصبح هي المتحكمة في نمو المدينة وليس العكس كما يحدث، وبالتالي القدرة على التخطيط للآجال والأجيال القادمة. Abstract: This study aims at identifying the urban growth process in one of the Algerian cities in light of the successive urban policies through the different historical stations that Algeria went through. Namely the city of Setif has known an accelerated urbanization led to the exhaustion of its real estate reserves The findings of the study confirmed that the urban policies in Setif as well the rest of the Algerian cities were confined in the economic conditions of the country. And in the majority of its phases it becomes no more than housing policies which focused on the quantity rather than the quality of life that go along the cultural composition of the Algerian society. Despite the efforts made by the state and the financial budgets that were spent, all these urban policies were responses to the city’s emergency problems. These urgent policies soon produce so many urban problems. Therefore, these policies have to be reconsidered in order to control the growth of the city and thus the ability to plan for the future generation.
مدينة سطيف إلى أين
Keywords: السياسات العمرانية; النمو الحضري; المدن الجزائرية; مدينة سطيف; The urban policies; The urban growth; Algerian cities; The city of Setif